1995
DOI: 10.1073/pnas.92.18.8244
|View full text |Cite
|
Sign up to set email alerts
|

Single-headed myosin II acts as a dominant negative mutation in Dictyostelium.

Abstract: Conventional myosin II is an essential protein for cytokinesis, capping of cell surface receptors, and development of Dictyostelium cells. Myosin II also plays an important role in the polarization and movement of cells. All conventional myosins are double-headed molecules but the significance of this structure is not understood since singleheaded myosin II can produce movement and force in vitro. We found that expression of the tail portion of myosin II in Dictyostelium led to the formation of single-headed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
3

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
2
18
3
Order By: Relevance
“…3). Based on equivalent modifications in Dictyostelium, mYFP- myosin II DN homodimers should completely lack actin binding and contractility, and the 'single headed' wild-type myosin/mYFP-myosin II DN heterodimers should have severely decreased actin binding and contractility (Burns et al, 1995;Uyeda and Yumura, 2000;Zang and Spudich, 1998). Consistent with this, we find that YFP-containing myosin isolated from mYFP-myosin II DN expressing Drosophila embryos shows reduced actin binding when compared with wild-type myosin in a standard spin down assay (see Fig.…”
Section: Functionally Distinct Modes Of Myosin Localizationsupporting
confidence: 70%
See 1 more Smart Citation
“…3). Based on equivalent modifications in Dictyostelium, mYFP- myosin II DN homodimers should completely lack actin binding and contractility, and the 'single headed' wild-type myosin/mYFP-myosin II DN heterodimers should have severely decreased actin binding and contractility (Burns et al, 1995;Uyeda and Yumura, 2000;Zang and Spudich, 1998). Consistent with this, we find that YFP-containing myosin isolated from mYFP-myosin II DN expressing Drosophila embryos shows reduced actin binding when compared with wild-type myosin in a standard spin down assay (see Fig.…”
Section: Functionally Distinct Modes Of Myosin Localizationsupporting
confidence: 70%
“…The PCR KpnI-XhoI central myosin fragment was inserted into the KpnI/XhoI-digested pBS-myosin-II-C-terminus backbone, to create myosin-II DN . This construct contains a dominant-negative form of myosin II, with the head removed at precisely the same point as an equivalent Dictyostelium myosin II DN [head-neck junction: amino acid 831 in Drosophila (QWWR) and position 809 in Dictyostelium (PWWK)] (Burns et al, 1995;Zang and Spudich, 1998). mYFP (Haseloff, 1999) (gift from J. Haseloff) was PCR amplified to introduce KpnI and NotI sites.…”
Section: Puast-myfp-myosin-ii Dnmentioning
confidence: 99%
“…A n alternate possibility considered at the outset of this study was that myosin II would still be able to form bipolar thick filaments in these cells, but the incorporation of L M M molecules into these filaments would disrupt their normal function. This idea was stimulated by our finding that the formation of single-headed myosin II in Dictyostelium cells leads to its incorporation into existent myosin filaments in a manner that disrupts myosin function in vivo (Burns et al, 1995). In contrast, the results described here illustrate that overexpression of LMM totally disrupts normal myosin filament formation by sequestering the native myosin II into abnormal aggregates.…”
Section: Discussioncontrasting
confidence: 39%
“…We attempted to obtain cell lines that expressed LMM at a lower level, however, analysis of many independent transformants indicated that all expressed the same high levels of LMM. In contrast, the levels of expression of other myosin tail fragments ($2 and Rod fragments) using the same vector reached only a 1:1 molar ratio with respect to the endogenous MHC (Burns et al, 1995).…”
Section: Expression Of Lmmmentioning
confidence: 98%
“…In Dictyostelium, myosin function has been disrupted genetically either by replacing the single myosin heavy chain gene with a truncated form or by removing it entirely (De Lozanne and Spudich, 1987;Manstein et al, 1989). Alternatively, myosin function can be reduced significantly by expressing antisense RNA or by expressing the carboxy-terminal rod domain of the protein (Knecht and Loomis, 1987;Burns et al, 1995). Regard-less of the method of disrupting myosin function, the phenotype is similar: cells lacking myosin cannot undergo cytokinesis when grown in suspension culture.…”
Section: Introductionmentioning
confidence: 92%